Nephrectomy with resection of the retrohepatic part of the inferior vena cava in a patient with kidney cancer and tumor thrombosis of the inferior vena cava - A. I. Babich; A. V. Osipov; A. I. Narkevich; A. Е. Demko (Вестник хирургии имени И.И. Грекова)
A clinical case of surgical treatment of renal cancer with tumor thrombosis of the inferior vena cava is presented. A rare operation was performed – nephrectomy and resection of the retrohepatic part of the inferior vena cava with a thrombus.